Clustered prosumer penalty framework on smart grid - Sumesh, S.; Potdar, Vidyasagar; Krishna, A. (2018)
© Springer Nature Singapore Pte Ltd. 2018. The smart grid regulators and retailers generally have a legally binding contract on purchasing energy from prosumers (energy producers). A hefty portion of them incorporate incentives strategies for energy effectiveness in their legal contract. In the event that the prosumers that supply energy meet or go past its objective, they will get a financial motivation, regularly an extent of the investment funds in energy rate that customers get. On the off chance that it misses the mark regarding the objective, it might be liable to a punishment. Thus, smart grid regulators reward well-performed prosumers or prosumer community groups using money earned from penalized poorly performed prosumers or prosumer community groups. Dissemination of punishments (penalties) assumes an essential part in prosumers. This can prompt fortifying existing non-dynamic energy sharing prosumers to end up dynamic prosumers. This paper proposes a performance-based penalty function technique that decidedly influences the way of the prosumers’ state of mind, along these lines bringing about a predictable energy sharing conduct.